Urban runoff control through Sustainable Urban Drainage Systems (SUDS): Wells / Infi ltration trenches (2019)
In the framework of the efficient managementof water resources and the environment, the control of thesurface run off is an area of study of great importance in the development of cities, because their exponential growth and the increase of non-permeable hard zones produces greater runoff transport times. Thus, environmental and economic implications are generated that leads to the implementation of mayor structures for the respective transport. When the control by these elements is not possible, flood phenomena aff ect thequality of life of the population and emergency plans for these risks must be generated. The implementation of alternative sustainable drainage systems such as Sustainable UrbanDrainage Systems (SUDS) allows to reduce and to delay thestorm surges that occur in. Next, an analysis of results relatedto hydraulic and hydrological modeling and the EPA-SWMM,a program developed by the United States EnvironmentalProtection Agency (EPA) for the analysis of rainfall andhydraulic behavior of networks of Sewerage